Pricing natural gas in Mexico: An application of the Little Mirrlees rule. The case of quasi-rents - Dagobert L. Brito; Juan Rosellón (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
In 1997, the Comisión Reguladora de Energía of Mexico implemented a netback rule for linking the Mexican natural gas price to the Texas price. At the time, the Texas price reflected a reasonably competitive market. Since that time, there have been dramatic increases in the demand for natural gas and there are various bottlenecks in the supply of natural gas. As a result, the price of natural gas in Texas now reflects the quasi-rents created by these bottlenecks. We address the optimality of the netback rule when the price of gas at the Texas market reflects the quasi-rents created by bottlenecks in the supply of natural gas to the United States pipeline system. In this paper, it is shown that it is optimal for the Mexican government to use the netback rule based on the Texas price of gas to set the price of natural gas in Mexico even though the Texas market cannot be considered a competitive market, and the Texas price for natural gas reflects quasi-rents created by various bottlenecks.
Keywords: Q40; L51; 330; Natural gas; welfare; pricing; Mexico; regulation